Analysis of Audience Reception towards Child-Free Discourse through Social Media - Rahmah, Salma Annisa; Hendariningrum, Retno; Yustitia, Senja (Jurnal The Messenger, 2024)
Introduction: Child-free is a person's decision not to have children. Child-free is a new value for the people of Indonesia. Gita Savitri Devi is an influencer who announced via Instagram and YouTube that she has decided to be child-free. This statement then caused controversy in the community. As a result, some parties are pro and contra against child-free. Methods: The method used is a qualitative method with a reception analysis approach. This study uses Stuart Hall's reception theory which divides the audience's meaning into dominant positions of hegemony, negotiation, and opposition. Findings: The results divide into four: accepting and desiring child-free, accepting and respecting child-free choices, opposing child-free discourse, and the audience trying to be neutral toward child-free discourse. The background behind the meaning is the place of residence, religion, education, occupation, and lifestyle owned by the audience, with the most common background tendency being the background of living. The reception in this study is that four informants are in a dominant position of hegemony, two informants are in a negotiating place, and one informant is in an opposition position, with the tendency of informants to be in a dominant part of hegemony. Originality: The results of this study can reveal how the audience interprets child-free discourse, which is a new perspective. In addition, it can be a development material for further researchers in examining the other side of the child-free phenomenon that has not yet appeared in this study.